2012
DOI: 10.4236/ajps.2012.310163
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability in Mixtures of Prairie Grass and Clovers

Abstract: Our objective was to evaluate the combining ability among cultivars of forage species, commonly sown in temperate regions of Argentina using a short rotation system. Three genetically diverse cultivars of prairie brome grass (Bromus catharticus, cv Copetona, cv Ñandú and cv Tango), a white clover cultivar (Trifolium repens, cv Lucero) and a red clover cultivar (T. pratense, cv Tropero) were evaluated. A randomized complete block design experiment was established in 2005. The treatments included five monocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Other findings also indicated that mixtures gave higher green forage yields than the pure stands [5] . This finding is in line with other scholars who reported that higher mean biomass yield was obtained from the mixture as compared to their components grown in monoculture [22] . Generally, the result shows that seeding ratio of 50:50 and 25:75 for alfalfa and Rhodes grass were showed the highest total biomass yields for the Rhodes grass and alfalfa in the intercropping system.…”
Section: Dry Matter Yieldsupporting
confidence: 93%
“…Other findings also indicated that mixtures gave higher green forage yields than the pure stands [5] . This finding is in line with other scholars who reported that higher mean biomass yield was obtained from the mixture as compared to their components grown in monoculture [22] . Generally, the result shows that seeding ratio of 50:50 and 25:75 for alfalfa and Rhodes grass were showed the highest total biomass yields for the Rhodes grass and alfalfa in the intercropping system.…”
Section: Dry Matter Yieldsupporting
confidence: 93%
“…Red clover can be established as a pure stand or in grass/legume mixtures, as a pasture for livestock. The cultivation of mixed grass/legume grasslands has been increasing because of many potential advantages in comparison to monocultures (Arturi et al, 2012). In Serbia, red clover is mostly grown in pure stands on arable land, but it is also seeded in grass mixtures, and occurs to a limited extent in permanent swards (Simić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This fixation of atmospheric nitrogen makes red clover an ideal rotational crop; particularly in organic agricultural systems where no synthetic nitrogen fertilizers are used [4]. A range of studies have observed that the establishment of red clover was more successful when sown in mixtures with grass species rather than in pure, monocultural stands [5,6]. In Estonia, the application of red clover in trials results in a mixed-species approach with other grass species blended to increase its commercial application value, where the complexity of estimation might be higher than monocropping systems.…”
Section: Introductionmentioning
confidence: 99%